Penggunaan Model Pembelajaran Berbasis Hands-on untuk Meningkatkan Keterampilan Menulis Paragraf Deskripsi pada Kelas X SMAN 9 Gowa - Ika Zulfika; Muhamamd Dahlan (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research is classroom action research (PTK). The aim of this research is to improve the ability to write descriptive paragraphs through a hands-on based learning model for class X students at SMAN 9 Gowa. The benefit of this research is that it can add to the scientific knowledge of language, the importance of teaching Indonesian, especially learning to write descriptive paragraphs. Apart from that, this research is expected to be useful for teachers, for students, for the author himself, and for research. The subjects of this research are class male and 7 female students. This research was carried out in two cycles, and each cycle was carried out in 4 meetings including a test at the end of each cycle. The data obtained was then analyzed using quantitative and qualitative analysis. The research results achieved after implementing the hands-on based learning model (1) can improve Indonesian language learning outcomes on the subject of descriptive paragraphs in class "low" from the ideal score of 100, while in cycle II there was an increase in the average score of 85.51, being in the high category with an ideal score of 100. (2) data from observations in each cycle showed a change in students' attitudes in a more positive direction. , namely students pay attention to the discussion of the material and students' ability to work on assignments individually increases. (3) Implementing Indonesian language learning on the subject of descriptive paragraphs using a hands-on based learning model can improve the skills of writing descriptive paragraphs in class X students at SMAN Gowa.